A New Tropical Species of Gracilariaceae (Rhodophyta, Gracilariales): Gracilaria silviae sp. nov. - Lyra, Goia De Mattos; Gurgel, Carlos Frederico Deluqui; Costa, Emmanuelle Da Silva; de Jesus, Priscila Barreto; Caires, Taiara Aguiar; de Matos, João Carlos Gama; Oliveira, Mariana Cabral; Oliveira, Eurico Cabral; Nunes, José Marcos De Castro (Phytotaxa, 2015)
A new flat species of Gracilaria, named Gracilaria silviae sp. nov., from the western Atlantic Ocean is described based on comparative morphological and molecular analyses of three molecular markers: the gene encoding cytochrome oxidase I (cox1), the Universal Plastid Amplicon (UPA) and the gene encoding the large subunit of ribulose-1, 5-bisphosphate carboxylase oxygenase (rbcL). Gracilaria silviae has a wide geographic distribution from the Indian River, Florida, USA, to Santa Catarina, southern Brazil, and a wide range of habit phenotypes. Across this geographic range Gracilaria silviae occupies a broad range of habitats, from warm temperate protected estuarine sublittoral areas to exposed tropical intertidal rocky shores and coastal reefs. The most morphologically similar species to G. silviae are not only the phylogenetically closest taxa to this species but also sympatric along its geographic range, i.e. G. tikvahiae and G. isabellana (formerly known as G. lacinulata in the northwestern Atlantic and G. tepocensis in southern Brazil).